2021
DOI: 10.11591/ijphs.v10i3.20777
|View full text |Cite
|
Sign up to set email alerts
|

The antihyperlipidaemic and hepatoprotective effect of Ipomoea batatas L. leaves extract in high-fat diet rats

Abstract: The administration of high-fat diets can increase the body's lipid level and damage the organs. Purple sweet potato leaf (Ipomoea batatas L.) was reported as an antioxidant against free radicals. This study aimed to observe the sweet potato leaf extract's activity on decreasing lipid profile and hepatoprotective effect in high-fat diet fed rats. The treatment animals were divided into five groups, namely normal control, high-fat diet (HFD) control, the treatment group of purple sweet potato leaf extract (SPLE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…The finding is also consistent with another previous study, which stated that purple sweet potato leaf extract was able to significantly reduce cholesterol and triglyceride levels and that it had a protective effect on the rat liver against damages from high-fat diets induction (Mahfudh et al, 2021). Purple sweet potato extract contains flavonoids that work by inhibiting cholesterol absorption, increasing bile excretion, and inhibiting HMG-CoA.…”
Section: Cholesterol and Triglyceride Levelssupporting
confidence: 93%
“…The finding is also consistent with another previous study, which stated that purple sweet potato leaf extract was able to significantly reduce cholesterol and triglyceride levels and that it had a protective effect on the rat liver against damages from high-fat diets induction (Mahfudh et al, 2021). Purple sweet potato extract contains flavonoids that work by inhibiting cholesterol absorption, increasing bile excretion, and inhibiting HMG-CoA.…”
Section: Cholesterol and Triglyceride Levelssupporting
confidence: 93%
“…ZC rhizome contains phenolic compounds, and the total phenolic content of ZC rhizome is 2.71 g GAE/100 g extract or 0.30 g GAE/100 g simplicia. In vivo research using 30 rats given ZC rhizome extract at a dose of 400 mg/kg showed a significant reduction in total cholesterol (Mahfudh et al, 2021).…”
Section: Effect Of Zc-psp Biscuits On Total Cholesterol Levels In Rat...mentioning
confidence: 97%
“…The antioxidant mechanism of curcumin is related to the presence of the H atom in the phenolic group. The action of curcumin as a radical scavenger is that it can maintain the integrity of cell membranes during oxidative degradation events due to the presence of oxygen radicals and other reactive radicals (Mahfudh et al, 2021).…”
Section: Effect Of Zc-psp Biscuits On Total Cholesterol Levels In Rat...mentioning
confidence: 99%
See 2 more Smart Citations